The Road to the Slaughter: ISIS Process of Dehumanizing the Enemy - Hamad Alqurainy, Sara; Hamedi M., Adnan; Usman Abubakar, Abubakar (Opción, 2019)
The so-called Islamic State is currently known as one of the greatest non-state security challenges of the 21st century. The organisation’s barbaric and inhuman treatments of its perceived enemies remain extremely shocking and totally unfath- omable to the sane humans. How ISIS succeeds in brainwashing its members to such inhuman acts requires deep study and analysis of the organisation’s messages in all forms and contexts. The aim of this paper, therefore, is to show how ISIS prepares its members to carry out heartless and cruel attacks on its foes. To achieve this objective, Sternberg’s Duplex Theory of hate is adopted as the framework of this paper. As proposed by Sternberg, Duplex Theory of hate consists of triangular structure namely, negation of intimacy, passion in hate, and commitment in hate. The paper collected 20 ISIS Arabic Twitter campaigns which were analysed the- matically with the aid of Nvivo 12 Pro software. Prior to the analysis, all 20 cam- paigns were transcribed, translated into English, and coded. This paper found that the Islamic State employs several strategies in an attempt to modify the behavior of its follower and potential recruits, thus, dehumanizing them in the process. Doing so prepares its followers to subject its enemies to the cruelest treatments of torture and often killing them.